Penerapan Model Problem Based Learning Berbantuan Canva pada Pembelajaran IPA Kelas V Sekolah Dasar - Ansya, Yusron Abda'u; Salsabilla, Tania (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study aims to describe the implementation of the Problem Based Learning model supported by the Canva application in science learning for fifth-grade elementary school students, as well as its impact on students' critical thinking skills and conceptual understanding. The research method used is a qualitative approach with a case study design. The study was conducted in the fifth grade of UPT SD Negeri 060809 Medan Kota during the 2022/2023 academic year, involving 30 students and a teacher experienced in utilizing learning technology. Data were collected through observations and in-depth interviews, then analyzed using thematic analysis techniques. The results show that the implementation of Problem Based Learning aided by Canva successfully increased student engagement in learning, developed critical thinking skills, and enhanced students’ understanding of scientific concepts such as environmental pollution. Furthermore, the use of Canva allowed students to present information creatively and interactively, which also contributed to the improvement of their communication skills. In conclusion, the Problem Based Learning model supported by technology such as Canva is not only effective in enhancing students' understanding of the material but also promotes collaboration and creativity. This study recommends the implementation of technology-based Problem Based Learning in science education as an innovative and relevant approach to address educational challenges in the digital era.